The fowl twins get what they deserve ebook - Colfer, Eoin (The Fowl Twins, 2021)
Irish Twins Myles and Beckett, Artemis Fowl's younger brothers, return in their third and most bizarre adventure yet. *"Like its bestselling progenitors, a nonstop spinoff afroth with high-tech, spectacular magic, and silly business."— Kirkus (starred review) For almost two years, Lord Teddy Bleedham-Drye, the Duke of Scilly, has been plotting revenge against the Fowl Twins, who humiliated him in Book One. Teddy plans to give them exactly what they deserve: permanent death. He threatens Myles with his weaponized jet and Beckett and Specialist Lazuli succeed in disarming the aircraft and causing an accident that kills the duke. But does it really? Ghosts, clones, and fairy magic come to play in this ultimate and ridiculous showdown between the twins and their worst enemy. Complete your middle grade fantasy collection with these best-selling fan favorites: Artemis Fowl by Eoin Colfer Airman by Eoin Colfer The Percy Jackson and the Olympians series by Rick Riordan Rick Riordan Presents The Storm Runner by J.C. CervantesArtemis Fowl is now a major motion picture streaming on Disney+